2016
DOI: 10.18632/oncotarget.13908
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of lncRNAs and mRNAs in patients with intracranial aneurysm

Abstract: Intracranial aneurysm (IA) is pathological dilatations of the cerebral artery and rupture of IAs can cause subarachnoid hemorrhage, which has a high ratio of fatality and morbidity. However, the pathogenesis of IAs remains unknown. We performed long noncoding RNA (lncRNA) and messenger RNA (mRNA) expression profiles in IA tissues and superficial temporal arteries (STAs). A total of 4129 differentially expressed lncRNAs and 2926 differentially expressed mRNAs were obtained from the microarrays (P < 0.05). Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 42 publications
(40 reference statements)
2
30
0
Order By: Relevance
“…MALAT1 has been documented to modulate smooth muscle dysfunction in thoracic aortic aneurysm [8]. Also, a study has presented the abnormal expression of lncRNAs and messenger RNA (mRNA) in IA, and the lncRNA-mRNA co-expression networks provide clues to find the pathogenesis of IA [9]. MALAT1 has been suggested to advance osterix expression and modulates osteogenic differentiation via targeting miRNA-143 (miR-143) expression in human bone marrow mesenchymal stem cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…MALAT1 has been documented to modulate smooth muscle dysfunction in thoracic aortic aneurysm [8]. Also, a study has presented the abnormal expression of lncRNAs and messenger RNA (mRNA) in IA, and the lncRNA-mRNA co-expression networks provide clues to find the pathogenesis of IA [9]. MALAT1 has been suggested to advance osterix expression and modulates osteogenic differentiation via targeting miRNA-143 (miR-143) expression in human bone marrow mesenchymal stem cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many articles have displayed of the critical roles played by lncRNAs, and it was suggested that lncRNAs are also implicated in cardiovascular diseases, such as aneurysms, myocardial infarction, and atherosclerosis . Furthermore, an lncRNA‐mRNA network was found to regulate inflammatory and immune responses, as well as the contraction of vascular smooth muscle and BSM . In a recent study, some RNA transcripts were shown to act as competing endogenous RNAs (ceRNAs) against miRNAs .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a luciferase reporter system to confirm the relationship between miR‐511 and lncRNA‐PAGBC. It was also shown that lncRNA‐PAGBC is implicated in the regulation of PIK3R3 and SOX4 level by binding with miR‐511 and miR‐133b, respectively . Therefore, we used the same reporter system to verify the regulatory relationship between miR‐511 and NOS1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors further performed lncRNA-mRNA co-expression network analysis (Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG)) and the co-expression networks were represented in immune response, inflammatory response, the muscle contraction pathway, and the vascular smooth muscle contraction pathway. There were 24 lncRNAs that interacted with eight mRNAs in the vascular smooth muscle contraction, 10 lncRNAs interacted with 10 mRNAs in the GO term of immune response, seven lncRNAs interacted with seven mRNAs in the GO term of inflammatory response, and 31 lncRNAs interacted with nine mRNAs in the muscle contraction pathway [27]. ANRIL, also known as CDKN2B-AS, is a long non-coding RNA mostly localized in the nucleus, spanning 126.3 kb in the genome, and its spliced product is a 3834 bp RNA [28].…”
Section: Lncrnas and Iasmentioning
confidence: 99%